Peristomal infection after percutaneous endoscopic gastrostomy: a 7-year surveillance of 297 patients - Duarte, Helena; Santos, Carla; Capelas, Manuel Luís; Fonseca, Jorge (IBEPEGE, 2012)
"Context - Healthcare-associated infection represents the most frequent adverse event during care delivery. Medical advances like percutaneous endoscopic gastrostomy have brought improvement on quality of life to patients but an increased risk of healthcare-associated infection. Predictive risk factors for peristomal wound infection are largely unknown but evidence suggests that antibiotic prophylaxis and preventive strategies related to infection control may reduce infection rates. Objectives - The primary aim was to evaluate the global prevalence rate of peristomal infection. Secondary objectives were to characterise the positive culture results, to evaluate the prophylactic antibiotic protocol and to identify potential risk factors for peristomal infection. Methods - Retrospective study of 297 patients with percutaneous endoscopic gastrostomy performed at a general hospital between January 2004 and September 2010. Patients received prophylactic cefazolin before the endoscopic gastrostomy procedure. Medical records were reviewed for demographic data, underling disease conditions to percutaneous endoscopic gastrostomy and patient potential intrinsic risk factors. Statistical analysis was made with the statistical program SPSS 17.0. Results - A total of 297 percutaneous endoscopic gastrostomy tubes were inserted. Wound infection occurred in 36 patients (12.1%). Staphylococcus aureus methicillin resistant was the most frequently isolated microorganism (33.3%) followed by Pseudomonas aeruginosa (30.6%). The incidence rate had been rising each year and differ from 4.65% in 2004/2007 to 17.9% in 2008/2010. This finding was consistent with the increasing of prevalence global infection rates of the hospital. Most of the infections (55.6%) were detected in the first 10 days post procedure. There was no significant difference in age, body mass index values, mean survival time and duration of percutaneous endoscopic gastrostomy feeding between patients with and without periostomal infection. Institutional factors, namely global prevalence infection rates and the endemic character of Staphylococcus aureus methicillin resistant, play an important role in peristomal infection rates. Traditional antibiotic prophylaxis with cefazolin is not adequate due to the prevalence of resistant organisms. Conclusions - Peristomal infection is a frequent problem with clinical impact in percutaneous endoscopic gastrostomy patients and should be considered a healthcare associated infection. The antimicrobial prophylaxis regimens using cephalosporins are not adequate and need to be reviewed due to the high prevalence of Staphylococcus aureus methicillin resistant and other resistant organisms in hospitals and nursing homes."
Keywords: Gastrostomy; Gastrointestinal endoscopy; Wound infection; Staphylococcus aureus; Antibiotic prophylaxis